Efficiency of Teaching Vocabulary in ESP Classes - Shoniyozovna, Doniyorova Gulrukh; Karamatovna, Ravshanova Nasiba; Kurbanovna, Abdieva Dilfuza; Sayfievna, Abdullaeva Shahlo ,; Mahliyo, Diyorova (International Journal of Psychosocial Rehabilitation, 2020)
ABSTRACT— Vocabulary learning is an important and indispensable part of any language learning process. It is the element, which links the four skills of speaking, listening, reading and writing all together. The author of this article focuses on the effective ways of teaching English vocabulary of the intermediate level students. Some ideas are taken from the books of such well-known researchers Folse, Harmer, Krashen, Allen that gives suggestions to teach English vocabulary effectively.